All the power in the world - Unger, Peter K (Oxford ; New York : Oxford University Press, 2006)
"This bold and original work of philosophy presents a new picture of concrete reality. Peter Unger breaks with what he terms the conservatism of present-day philosophy, and returns to central themes from Descartes, Locke, Berkeley, Hume and Russell. Wiping the slate clean, Unger works, from the ground up, to formulate a new metaphysic capable of accommodating our distinctly human perspective. He proposes a world with inherently powerful particulars of two basic sorts: one mental but not physical, the other physical but not mental."
"All the Power in the World takes readers on a philosophical journey into the nature of reality. In this intellectual adventure, Unger reveals the need for an entirely novel approach to the nature of physical reality - and shows how this approach can lead to wholly unexpected possibilities, including disembodied human existence for billions of years. All the Power in the World returns philosophy to its most ambitious roots in its fearless attempt to answer profoundly difficult human questions about ourselves and our world."--Jacket
The mystery of the physical -- A humanly realistic philosophy -- Demystifying the physical -- A cornucopia of quality -- A plenitude of power -- Is free will compatible with scientiphicalism? -- Why we really may be immaterial souls -- Why we may become disembodied but to no avail -- The problem of our unconscious quality -- How rich is concrete reality?
Includes bibliographical references (pages 623-627) and index
Keywords: Metaphysics; Reality; Physics -- Philosophy; Metaphysics